2015
DOI: 10.1038/jid.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

The High Expression of the microRNA 17–92 Cluster and its Paralogs, and the Downregulation of the Target Gene PTEN, Is Associated with Primary Cutaneous B-Cell Lymphoma Progression

Abstract: The oncogenic microRNA (miR) 17-92 cluster has a causative role in the lymphomagenesis of nodal B-cell lymphomas, by activating proliferation and inhibiting apoptosis. Here we analyzed primary cutaneous B-cell lymphomas for the miR-17-92 cluster and its paralogs miR-106a-363 and miR-106b-25. In 22 primary cutaneous diffuse large B-cell lymphomas, leg type (PCLBCL-LT) compared with 22 primary cutaneous follicle center lymphomas (PCFCLs), we found that miR-20a and miR-106a were overexpressed. Multivariate Cox an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Based on the mechanism of miRNA function, the OncomiRs can target a varity of onco-suppressor genes and inhibit their post-transcriptional expression. For example, PTEN (phosphate and tensin homolog) is a tumor suppressor gene, which was regulated by several miRNAs, such as miR-21 [12], miR-155 [13], miR-221/222 [14], and miR-17~92 cluster [15]. In DLBCL, the high-expressed OncomiRs bind to PTEN mRNA and inhibit its expression.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mechanism of miRNA function, the OncomiRs can target a varity of onco-suppressor genes and inhibit their post-transcriptional expression. For example, PTEN (phosphate and tensin homolog) is a tumor suppressor gene, which was regulated by several miRNAs, such as miR-21 [12], miR-155 [13], miR-221/222 [14], and miR-17~92 cluster [15]. In DLBCL, the high-expressed OncomiRs bind to PTEN mRNA and inhibit its expression.…”
Section: Introductionmentioning
confidence: 99%
“…22,25,27,28 However, there has been limited research to define the underlying mechanism. The Bim gene expression was inversely associated with miR-20a-5p, suggesting it could be a target gene of miR20a-5p.…”
Section: Mir-20a-5p Regulates Bim Expression Via Jnk2mentioning
confidence: 99%
“…20 This cluster is frequently overexpressed in human cancers and has been shown to promote several aspects of oncogenic transformation, including proliferation and evasion of apoptosis. 21,22 Among the members of miR-17 family, miR-20a has been extensively studied on its role in tumor development and progression. It was reported that miR-20a was up-regulated in anaplastic thyroid cancer, 23 and it could promote gastric cancer cell proliferation and inhibit cell apoptosis via post-transcriptional modulation of p21 and TP53INP1.…”
Section: Introductionmentioning
confidence: 99%
“…miR-20b also regulates the expression of the proteinase-activated receptor-1 (PAR-1) thrombin receptor in melanoma cells [12]. It has been demonstrated to regulate several cancers, including gastric [13], liver [14], cervical [15], colon [16], lung [17], and lymphoma [18]. However miR-20b's function in thymoma development and implications of thymoma in myasthenia gravis pathophysiology have not been previously systematically investigated.…”
Section: Introductionmentioning
confidence: 99%